RESPIRATORY DISEASE INCIDENCE IN WORKERS OF SYLVINITE PROCESSING ENTERPRISE - Богданович, Ксения Викторовна (Medicine in Kuzbass, 2025)
The study aim was to analyze disease incidence with temporary disability due to respiratory diseases at the sylvinite processing enterprise.Materials and methods. 5274 cases of temporary disability of workers of the sylvinite processing enterprise caused by a group of respiratory diseases were analyzed using the method of in-depth analysis of the disease incidence with temporary disability according to personal («individual») accounting with the calculation of relative risk and etiological fraction to determine the industrial causality of the disease incidence level (using a control group of workers, not exposed to harmful factors).Results. The values of the indices for the number of cases and the number of days of temporary disability per 100 workers, as well as the average duration of one case in different years of the analyzed period were higher than the normalizing indicators for the chemical and petrochemical industries. Respiratory diseases as a cause of temporary disability occupied the first rank in the structure of cases and days of disability in the analyzed enterprise subdivisions. Among the individual nosological forms of respiratory diseases, acute respiratory infections of the upper respiratory tract made a leading contribution to the number of cases and days of temporary disability, and long-term cases of temporary disability were noted in this group. The values of the relative risk and etiological fraction indices for the group of respiratory diseases in certain enterprise subdivisions indicate an average and high degree of industrial causality of a higher disease incidence level with temporary disability.Conclusion. The possibility of the development of industrial-related diseases among the workers of sylvinite processing enterprise determines the need to elaborate a set of medical preventive measures aimed at reducing the disease incidence with temporary disability in the group of respiratory diseases.
Keywords: processing of sylvinite; disease incidence with temporary disability; industrial-related incidence; respiratory diseases; relative risk; etiological fraction